2005
DOI: 10.1128/mcb.25.16.7226-7238.2005
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae as a Model System To Define the Chromosomal Instability Phenotype

Abstract: Translocations, deletions, and chromosome fusions are frequent events seen in cancers with genome instability. Here we analyzed 358 genome rearrangements generated in Saccharomyces cerevisiae selected by the loss of the nonessential terminal segment of chromosome V. The rearrangements appeared to be generated by both nonhomologous end joining and homologous recombination and targeted all chromosomes. Fifteen percent of the rearrangements occurred independently more than once. High levels of specific classes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
64
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 113 publications
(116 reference statements)
7
64
1
Order By: Relevance
“…One important method in this category is the gross chromosomal rearrangement (GCR) assay developed by the Kolodner laboratory, which is based on the selection against two markers near the left end of chromosome V in budding yeast (Chen and Kolodner 1999). The rearrangement breakpoints in hundreds of GCR-containing strains have been mapped, although doing such mapping one strain at a time is a time-and cost-consuming endeavor (Putnam et al 2005;Chan and Kolodner 2012).…”
Section: Comparison With Other Methods That Can Reveal Dna Lesion Hotmentioning
confidence: 99%
“…One important method in this category is the gross chromosomal rearrangement (GCR) assay developed by the Kolodner laboratory, which is based on the selection against two markers near the left end of chromosome V in budding yeast (Chen and Kolodner 1999). The rearrangement breakpoints in hundreds of GCR-containing strains have been mapped, although doing such mapping one strain at a time is a time-and cost-consuming endeavor (Putnam et al 2005;Chan and Kolodner 2012).…”
Section: Comparison With Other Methods That Can Reveal Dna Lesion Hotmentioning
confidence: 99%
“…Most of the translocation events described are mediated by no homology at the break point or very short sequence homologies and are dependent on DNL4, an essential component of the NHEJ pathway. 37 In the absence of both RAD52 and DNL4 the translocation class of GCRs is eliminated. An unusual class of translocations is detected between highly diverged sequences in the absence of the Sgs1 helicase and at least one other protein involved either in the DNA damage checkpoint response, chromatin assembly or the DNA unwinding.…”
Section: Bir and Gcrsmentioning
confidence: 99%
“…For both the translocations and interstitial deletions, the rate of events in a wild-type strain is very low (,10 29 /division); the breakpoints of the events occur between CAN1 and PCM1 and typically involved micro-or no sequence homology. Most of these rearrangements reflect nonhomologous end-joining (NHEJ) events, although homologous-recombination (HR) events involving very small homologies are also observed (Putnam et al 2005). More recent versions of the GCR assay showed that the introduction of homology either from a dispersed repeated gene family member (HXT13) or from a Ty element inserted between CAN1 and PCM1 elevated the rate of URA3-CAN1 codeletions by two to three orders of magnitude.…”
mentioning
confidence: 99%